COLLABORATION FOR MANAGING DISASTER EMERGENCIES THROUGH THE LASER WARE PROGRAM - Abdullah, Muh Yusuf; Uluputty, Irfan (Jurnal Pemerintahan Dan Keamanan Publik (JP dan KP), 2024)
Handling disaster emergencies with the Integrated Emergency Management System through the LAKA SI LASER program has the aim of exploring the collaborative process of handling disaster emergencies that occur in Pinrang Regency. Handling disaster emergencies through the LAKA SI LASER program refers to the concept of collaborative governance put forward by Emerson. The three dimensions measured are collaboration dynamics, collaborative actions, impact and adaptation of the LAKA SI LASER program. Qualitative research method with a case research approach that explores information on handling disaster emergencies within the Pinrang Regency BPBD and agencies involved in handling disaster emergencies. Strengthening case studies using data triangulation. Collaboration through the LAKA SI LASER program shows the fact that in dealing with disaster emergencies, not involving all agencies in the LAKA SI LASER program to handle disaster emergencies and also minimal facilities for handling disaster emergencies. However, the collaboration carried out provides benefits for each agency participating in the collaboration to handle disaster emergencies. Keywords: Collaboration, Disaster Emergency, LAKA SI LASER.